PENGARUH AROMATERAPI TERHADAP PENURUNAN TEKANAN DARAH PADA PASIEN DENGAN HIPERTENSI : LITERATURE REVIEW - Roswita, Ria (Politeknik Kementerian Kesehatan Banjarmasin, 2022)
Abstract: Hypertension is a cardiovascular disease that causes the most death and is increasing every year. The prevalence of hypertension in Indonesia tends to increase in all provinces. One of the non-pharmacological hypertension interventions that can be done is aromatherapy. This study is a literature review that aims to determine the effect of aromatherapy on reducing blood pressure in hypertensive patients. This literature review analyzes 13 articles from journal databases, such as Google Schollar, Proquest and Science Direct with the keywords